2012
DOI: 10.1186/1471-2407-12-283
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of quality of life effects in patients undergoing palliative radiotherapy for brain metastases

Abstract: BackgroundRecently published results of quality of life (QoL) studies indicated different outcomes of palliative radiotherapy for brain metastases. This prospective multi-center QoL study of patients with brain metastases was designed to investigate which QoL domains improve or worsen after palliative radiotherapy and which might provide prognostic information.MethodsFrom 01/2007-01/2009, n=151 patients with previously untreated brain metastases were recruited at 14 centers in Germany and Austria. Most patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 36 publications
2
53
2
3
Order By: Relevance
“…Following a pre-planned interim analysis, the rules for futility were met, with a mean score of hair loss exceeding 56.7 on the EORTC BN20 (mean score of 95). The score of hair loss in our study was higher than in the literature, where in general scores between 30 and 40 are reported [4,6,26,27]. In the study of Steinman et al and Slotman et al, 42% and 22% of patients showed an increase in hair loss scores exceeding 20 points, respectively, compared to all patients in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…Following a pre-planned interim analysis, the rules for futility were met, with a mean score of hair loss exceeding 56.7 on the EORTC BN20 (mean score of 95). The score of hair loss in our study was higher than in the literature, where in general scores between 30 and 40 are reported [4,6,26,27]. In the study of Steinman et al and Slotman et al, 42% and 22% of patients showed an increase in hair loss scores exceeding 20 points, respectively, compared to all patients in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…This study's finding of an average OS of 5.27 months (SD = 4.89) is similar to survival times in earlier studies (Andrews et al, 2004;Lin et al, 2013;Rades et al, 2008;Steinmann et al, 2012). Andrews et al (2004) determined that median survival was 6.7 months in patients with multiple metastases in a WBRT-alone group, whereas Steinmann et al (2012) noted that median OS was 4.5 months.…”
Section: Discussionsupporting
confidence: 87%
“…Eine große prospektive Studie mit 151 Patienten (90 Bronchialkarzinome, 25 Mammakarzinome, 12 Melanome), die sich wegen multipler Hirnmetastasen einer palliativen Ganzhirnbestrahlung unterziehen mussten, bestätigte die Verschlechterung der Lebensqualität 3 Monate nach der Radiotherapie, vor allem die Verschlechterung der allgemeinen und körperlichen Funktionen [8]. Die Lebensqualität wurde mit dem Kurzfragebogen QLQ-C15-PAL und dem Hirnmodul BN20 erhoben.…”
Section: Stereotaxie In Der Therapie Von Zns-metastasen?unclassified